1999
DOI: 10.1080/104732299302332
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Sampling and Analytical Methods for Assessing Occupational Exposure to Diesel Exhaust in a Railroad Work Environment

Abstract: Methods of assessing occupational exposure to diesel exhaust were evaluated in a railroad work environment. The American Conference of Governmental Industrial Hygienists (ACGIH)-recommended elemental carbon and respirable combustible dust methods of sampling and analysis for assessing diesel exhaust were included in the study. A total of 215 personal and area samples were collected using both size-selective (nylon cyclone and Marple) and non-size-selective samplers. The results demonstrate that the elemental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
3
23
2
Order By: Relevance
“…However, Verma et al (1999) observed corresponding mean EC levels of from 4.4 to 17.8 lg/m 3 for the different exposure groups, which are much lower than the ARP levels reported by Woskie et al (1988a). Importantly, Verma et al (1999) showed that the exposure to EC was a minor part (2% to 16%) of railroad workers' exposure to respirable PM. Results are summarized in Table 3.…”
Section: Railroad Workerscontrasting
confidence: 65%
See 3 more Smart Citations
“…However, Verma et al (1999) observed corresponding mean EC levels of from 4.4 to 17.8 lg/m 3 for the different exposure groups, which are much lower than the ARP levels reported by Woskie et al (1988a). Importantly, Verma et al (1999) showed that the exposure to EC was a minor part (2% to 16%) of railroad workers' exposure to respirable PM. Results are summarized in Table 3.…”
Section: Railroad Workerscontrasting
confidence: 65%
“…DE particles are primarily carbon and the EC method was developed subsequent to the study by Woskie et al (1988aWoskie et al ( , 1988b to reduce interference from other sources. A more recent industrial hygiene study of exposure to DE in a railroad work environment by Verma et al (1999) found total respirable PM concentrations in the same range as those reported by Woskie et al (1988a). However, Verma et al (1999) observed corresponding mean EC levels of from 4.4 to 17.8 lg/m 3 for the different exposure groups, which are much lower than the ARP levels reported by Woskie et al (1988a).…”
Section: Railroad Workerssupporting
confidence: 61%
See 2 more Smart Citations
“…The results of the source characterization and source apportionment have been published in report form by Zielinska et al (2001) and will be submitted for publication in peer-reviewed literature. Previous studies on the composition of mine aerosols have focused primarily on the size distribution and EC content of mines (Tomb and Haney 1995;Birch and Cary 1996;Verma et al 1999). More comprehensive measurements made during the current study re ect the composition of the major contributors to mine air.…”
Section: Introductionmentioning
confidence: 86%